Determinan jumlah penduduk miskin di Barlingmascakeb tahun 2012-2019 - Corolina, Natalia Nola; Sarfiah, Sudati Nur; Panjawa, Jihad Lukis (Journal of Economics Research and Policy Studies, 2021)
Creating a just, prosperous, and equitable life is the ultimate development goal in every country. Poverty is one of the problems in development and hinders these development goals. Barlingmascakeb is one of the development areas in Central Java province, which has a high number of poor people and poverty. This study aimed to analyze the effect of gross regional domestic product, inflation rate, human development index, and open unemployment rate on the poor population. The analytical method used in this research is panel data regression with a fixed-effect model approach. The results showed that the gross regional domestic product and the human development index had a significant adverse effect on the poor. The open unemployment rate had a significant positive effect on the number of the poor, and the inflation rate did not affect the number of the poor. The government’s role is needed to improve welfare, maintain the stability of the inflation rate, improve the quality of human development programs and increase training and skills programs to reduce the number of poor people.